Forming Multimodal Transportation Companies: Barriers, Benefits, and Problems : A Conference - Whitehurst, Clinton H.; American Enterprise Institute for Public Policy Research (Washington: American Enterprise Institute for Public Research, 1978)
This conference stemmed from a unanimous decision that progress in transportation can be made only by thoughtful exploration of the advantages and disadvantages of a proposal, by the exchange of views among the interested elements of the transportation community, and by frank recognition of the political problems inherent in any change; after several talks about multimodal transportation (barriers, benefits, and problems) amongst transport regulatory bodies.
Proceedings of a conference sponsored by the Institute, held in Washington, D.C., Feb. 1978.
Includes index.
Bibliography: p. 171-179.
ne 23/02/2018
Loan
Keywords: Carriers; Transportation; Corporation Law